PENGARUH AKTIVITAS FISIK DAN POLA MAKAN TERHADAP KADAR GULA DARAH PADA PASIEN DIABETES MELLITUS - Abdul Qodir (LPPMK STIKES Widyagama Husada, 2022)
Background: Diabetes mellitus is a non-communicable disease that can be controlled by doing regular physical activity and maintaining a healthy diet. Physical activity and maintaining a diet are carried out so that the blood sugar levels of patients with diabetes mellitus can be controlled. Aim : To determine the effect of physical activity and diet on blood sugar levels in patients with diabetes mellitus based on empirical studies in the last 5 years. Method : This study uses the PICOS framework method, searching for articles using Google Scholar and Science Direct in the last 5 years obtained 14 Indonesian and English-language journals with keywords in the search that match the inclusion and exclusion criteria. Result : Based on 14 search journals, the results of research on physical activity and diet on blood sugar levels were obtained. Physical activity that is carried out regularly is one of them by walking around the house and with eating patterns that pay attention to the 3h pattern (right schedule, type and amount of food). Conclusion: There is a relationship between physical activity and diet on blood sugar levels in patients with diabetes mellitus. The recommended physical activity is one of them walking around the house for 30-40 minutes. Meanwhile, the recommended eating pattern is to pay attention to the 3j pattern (right schedule, type and amount of food) with a schedule of 3 large meals and 3 snacks. Keywords: Diabetes mellitus;physical activity;diet;sugar levels